2019
DOI: 10.1186/s42358-019-0062-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison among ACR1997, SLICC and the new EULAR/ACR classification criteria in childhood-onset systemic lupus erythematosus

Abstract: Background: To date there are no specific classification criteria for childhood-onset systemic lupus erythematosus (cSLE). This study aims to compare the performance among the American College of Rheumatology (ACR) 1997, the Systemic Lupus International Collaborating Clinics criteria (SLICC) and the new European League Against Rheumatism (EULAR)/ACR criteria, in a cSLE cohort. Methods: We conducted a medical chart review study of cSLE cases and controls with defined rheumatic diseases, both ANA positive, to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 25 publications
2
28
0
3
Order By: Relevance
“…We are grateful to Fonseca and colleagues for their efforts to test the new criteria in a South American pediatric population and for their reiteration that leukopenia in patients of African descent is common and may lead to misclassification if not correctly attributed to ethnicity. The significant prevalence of SLE‐specific items in their non‐SLE patient population , however, sheds doubt on the correct use of the EULAR/ACR 2019 SLE classification criteria attribution rule or, less likely, the non‐SLE diagnoses in this cohort. This may explain some of the discrepancies between their cohort and the EULAR/ACR SLE criteria validation cohort.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…We are grateful to Fonseca and colleagues for their efforts to test the new criteria in a South American pediatric population and for their reiteration that leukopenia in patients of African descent is common and may lead to misclassification if not correctly attributed to ethnicity. The significant prevalence of SLE‐specific items in their non‐SLE patient population , however, sheds doubt on the correct use of the EULAR/ACR 2019 SLE classification criteria attribution rule or, less likely, the non‐SLE diagnoses in this cohort. This may explain some of the discrepancies between their cohort and the EULAR/ACR SLE criteria validation cohort.…”
mentioning
confidence: 85%
“…While unfortunately details on the exact distribution of the EULAR/ACR criteria items were not provided by Fonseca et al , the data on the SLICC criteria items listed suggest that item attribution for the EULAR/ACR criteria may not have been correctly performed. For example, 25% of the non‐SLE patients in their sample had an acute cutaneous lupus erythematosus (ACLE) rash . If this were true ACLE by the EULAR/ACR definition (“Malar rash or generalized maculopapular rash observed by a clinician.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Our group recently published a study that assessed the performance of the new EULAR/ACR classification criteria in a population with childhood‐onset SLE and controls with other defined rheumatic diseases that often are difficult to distinguish from childhood‐onset SLE in daily clinical practice . Both our childhood‐onset SLE group and the control patients were all positive for ANA, which may constitute an external validation since the original derivation and validation cohorts did not include patients with childhood‐onset SLE, as stated by Aringer et al .…”
Section: Performance Measures For the New Eular/acr Criteria In Classmentioning
confidence: 99%
“…A recent study reported that, if the cut-off score was changed to 13, it would result in a higher specificity, positive predictive value, and cut-off point accuracy. 15 Therefore, in this study, we also desired to explore proper modification of EULAR/ACR’19.…”
Section: Introductionmentioning
confidence: 99%